The last wagon train - Johnstone, William W.; Johnstone, J. A. (Pinnacle Books / Kensington Publishing Corp., 2024)
A new railroad line is coming to Hansen’s Bend—and the Old West will never be the same. Especially for the Callahans. They’ve been running the local wagon train outfit for years. But now a pompous rail boss named Arbuckle wants to put them out of business.